Efficacy, but not antibody titer or affinity, of a heroin hapten conjugate vaccine correlates with increasing hapten densities on tetanus toxoid, but not on CRM(197) carriers - Jalah, Rashmi (Bioconjug Chem, 2015)
Vaccines against drugs of abuse have induced antibodies in animals that blocked the biological effects of the drug by sequestering the drug in the blood and preventing it from crossing the blood-brain barrier. Drugs of abuse are too small to induce antibodies and, therefore, require conjugation of drug hapten analogs to a carrier protein. The efficacy of these conjugate vaccines depends on several factors including hapten design, coupling strategy, hapten density, carrier protein selection, and vaccine adjuvant. Previously, we have shown that 1 (MorHap), a heroin/morphine hapten, conjugated to tetanus toxoid (TT) and mixed with liposomes containing monophosphoryl lipid A [L(MPLA)] as adjuvant, partially blocked the antinociceptive effects of heroin in mice. Herein, we extended those findings; demonstrating greatly improved vaccine induced antinociceptive effects up to 3% mean maximal potential effect (%MPE). This was obtained by evaluating the effects of vaccine efficacy of hapten 1 vaccine conjugates with varying hapten densities using two different commonly used carrier proteins, TT and cross-reactive material 197 (CRM(197)). Immunization of mice with these conjugates mixed with L(MPLA) induced very high anti-1 IgG peak levels of 400 – 1,500 µg/mL that bound to both heroin and its metabolites, 6-acetylmorphine and morphine. Except for the lowest hapten density for each carrier, the antibody titers and affinity were independent of hapten density. The TT carrier based vaccines induced long-lived inhibition of heroin-induced antinociception that correlated with increasing hapten density. The best formulation contained TT with the highest hapten density of ≥30 haptens/TT molecule and induced %MPE of approximately 3% after heroin challenge. In contrast, the best formulation using CRM(197) was with intermediate 1 densities (10–15 haptens/ CRM(197) molecule), but the %MPE was approximately 13%. In addition, the chemical synthesis of 1; the optimization of the conjugation method; and the methods for the accurate quantification of hapten density are described.